Singular p-biharmonic problem with the Hardy potential - Drissi, Amor; Ghanmi, Abdeljabbar; Repovš, Dušan D. (Nonlinear Analysis: Modelling and Control, 2024)
The aim of this paper is to study existence results for a singular problem involving the p-biharmonic operator and the Hardy potential. More precisely, by combining monotonicity arguments with the variational method, the existence of solutions is established. By using the Nehari manifold method, the multiplicity of solutions is proved. An example is also given to illustrate the importance of these results.